Analysis of Bottled Drinking Water Distribution Routes Using the Vehicle Routing Problem (Case Study: PT Sabina Tirta Utama Samarinda) - Nurlita, Nabila; Wahyuda, Wahyuda; Utomo, Dutho Suh (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
PT Sabina Tirta Utama is a bottled drinking water production company located at Mas Penghulu street, Samarinda city. In addition to producing Bottled Drinking Water, this company also distributes its products to agents and end customers. The company has 4 units of Daihatsu Gran Max Pick Up vehicles that are used in the distribution of bottled drinking water with a maximum capacity of 200 boxes. The company's most customers are in Samarinda City. Because this company distributes its products, it must determine the route traveled to meet customer demand. One solution to overcome the problems at PT Sabina Tirta Utama Samarinda is to use the Vehicle Routing Problem, which is a method of solving distribution problems by considering the limited capacity of vehicles. In solving Vehicle Routing Problem, several methods are used, namely the Saving Matrix, Nearest Neighbor, and Insertion methods. Based on the research results, the total initial distribution distance is 117.53 km with an initial route of 10 routes and distribution costs of IDR979.417/month. In the Saving Matrix method, the total distance can be optimized to 107,55 km with 7 routes. After sorting customers using Nearest Neighbor, the total distance is 103,13 km, while the Insertion method gets a total distance of 90,24 km. Of the three methods, the most optimal total distance is 90,24 km, namely by using the Insertion method. So that the company can save a distance of 23% of the company's initial distance. Therefore, the company can save gasoline fuel costs from IDR979.417 to IDR752.000 with a difference of IDR227.417/month.